STRATEGI QIRA'AH DALAM PEMBELAJARAN BAHASA ARAB DI MI - Mita Nuril Fauzia; Taufik (STQINIS, 2024)
This research is motivated by problems related to reading strategies in Arabic language learning. Starting from getting to know more closely what a strategy is to what is called a laearning strategy, what are the objectives of reading strategies in learning Arabic, especially in Islamic elementary schools or beginner level, and various kinds of reading strategies in an effort to achve maximum results in the language learning process Arabic, especially at Islamic elementary school. In exploring this reasearch, the researcher conducted a library study or library research to help make it easier to find references wich could be in the form of books and journals. So, in the results the researcher raised several reading strategies that can be used in learning Arabic at Islamic elementary school, including: 1) reading aloud, 2) reading silently 3) reading quickly, 4) recreational reading, 5) analytical reading